Review: Novel sources and functions of microbial lipases and their role in the infection mechanisms - Pascoal, Ananias (2018)
Lipases belong to the family of serine hydrolases, which in turn include various esterase enzymes (E.C.3.1.1.1). They are involved in the cleavage of triacylglycerols to free fatty acids and glycerol in many important biological processes, as for instance routine metabolism of dietary triglycerides to cell signalling and inflammation. Lipases constitute a ubiquitous group of enzymes able to catalyse a number of different reactions, many of them of industrial interest. Particularly, microbial lipases exhibit a wide range of industrial applications, namely in pharmaceutical, food and detergents industry. The aim of this review is to summarize the recent achievements illustrating the importance and the versatility of microbial lipases, including their involvement in infection mechanisms.